A new species of Clavariadelphus (Basidiomycota: Clavariadelphaceae) from China based on morphological and molecular data - Xia, Lu; Fan, Li (Phytotaxa, 2020)
Clavariadelphus griseoclavus sp. nov. is described and illustrated from North China. Morphologically, the new species is distinguished from other Clavariadelphus species by its grey to greyish basidiomata. Molecular phylogenetic analysis based on ITS sequences is provided and supports the establishment of the new species.